SAT0544 Sedentary Time Among Adults with Rheumatoid Arthritis. The Para 2010 Study. (23rd January 2014) - Åsenlöf, P.; Bergman, P.; Demmelmaier, I.; Jensen, I.; Nordgren, B.; Opava, C. H.
Abstract : Background: Sedentary behavior may introduce serious health threats in persons with rheumatoid arthritis (RA) since this condition is associated with an increased risk of cardiovascular morbidity and mortality. The prevalence and correlates of sedentary behavior in the RA population are still to be uncovered. Objectives: To describe amount of self-reported daily time spent sedentary and to identify variables explaining its variation in a large, well-defined sample of adults with RA. Methods: A sample of 3152 individuals (73 % women, mean age 62 years) was identified via the Swedish Rheumatology Quality registers (SRQ) and participated in this cross-sectional study. Sedentary time was assessed with the International Physical Activity Questionnaire (IPAQ); one item measuring daily time spent sitting in hours and minutes during the past week. Data were retrieved from the SRQ and from a mailed package of established questionnaires and study-specific questions on sociodemographics, disease-related variables, physical activity, and psychosocial variables. A multinomial logistic regression analysis based on multiple imputations of missing data was applied. Results: Time spent sedentary was reported to a median of 240 minutes (4 hours) per day (Q1 = 65 minutes, Q3 = 360 minutes). The regression model explained 16.7% (Nagelkerke pseudo r 2 ) of the variation in sedentary time. After adjustments for all other independent variables, statistically significantly higher odds for spending more time sedentary were found for men, younger ages, higher education, lower income, members of families with no children below 18 years, good Swedish language comprehension, low to moderate pain intensity, higher activity limitation, higher self-efficacy for exercise, lower outcome expectations regarding the long-term effects of health enhancing physical activity on general health, and non-adherence to physical activity recommendations. Conclusions: This is the first study describing sedentary time in persons with RA as a construct separated from physical activity level. One possible explanation for the relatively short time spent sedentary during daytime might be that individuals with RA go to bed early due to fatigue and remain longer in bed due to morning stiffness, thus leaving less time for daytime activities including sitting. Our result indicates that variation in sedentary time is explained by a unique set of variables that are not necessarily the same as those previously identified to explain variation in physical activity (1). Sedentary behaviors may thus deserve particular attention during consultations. Means to promote prolonged standing, interrupted sitting time, and non-exercise activity thermogenesis (e.g. gardening, household chores, short walks) should be considered and evaluated in future studies. References: Demmelmaier I, Bergman P, Nordgren B, Jensen I, Opava CH. Current and maintained health-enhancing physical activity in rheumatoid arthritis. The PARA 2010 study. Arthritis Care Res 2013 Jan 17 [Epub ahead of print]. Disclosure of Interest: None Declared